Evaluation of the environmental management system of a printed circuit board manufacturing company - Phoon, Chee Weng. (2008)
This dissertation evaluated how a local PCB company managed the wastes, by looking at the generation of the wastes, the handling methods, the waste minimisation practices in place and the suggestions that can improve the waste management system.